1997
DOI: 10.1042/bj3240981
|View full text |Cite
|
Sign up to set email alerts
|

Increased flux through the hexosamine biosynthesis pathway inhibits glucose transport acutely by activation of protein kinase C

Abstract: The hexosamine biosynthesis pathway and protein kinase C (PKC) activation mediate hyperglycaemia-induced impaired glucose transport, but the relative role of each pathway is unknown. Following a 2 h preincubation of rat adipocytes in the presence of either high glucose (30 mM) plus insulin (0.7 nM) or glucosamine (3 mM), both high glucose and glucosamine inhibited subsequent basal and insulin-stimulated glucose transport, measured at 5.0 mM glucose. Azaserine, an inhibitor of the enzyme glutamine:fructose-6-ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
28
1

Year Published

1999
1999
2004
2004

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 34 publications
(26 reference statements)
3
28
1
Order By: Relevance
“…Furthermore hexosamines promote Sp1 O-linked N-acetylglucosamine glycosylation [33], which stabilizes this transcription factor, increasing its cellular concentrations [34]. Several other studies have proposed a role of the HBP in PKC activation in different cell types [19,35,36,37], and PKC has been shown to mediate glucose-induced p38-MAPK activation [38], confirming our results in control transfected cells.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore hexosamines promote Sp1 O-linked N-acetylglucosamine glycosylation [33], which stabilizes this transcription factor, increasing its cellular concentrations [34]. Several other studies have proposed a role of the HBP in PKC activation in different cell types [19,35,36,37], and PKC has been shown to mediate glucose-induced p38-MAPK activation [38], confirming our results in control transfected cells.…”
Section: Discussionsupporting
confidence: 90%
“…Transient overexpression of GFAT leads to insulin resistance indicating that this pathway could also be activated in skeletal muscle of glucose infused rats [72]. Of note, recent results showed that activation of this pathway leads to activation of PKC [21] and induces translocation of the PKC isoforms a, e and particularly b, but not z [73] supporting the possibility of an involvement of the hexosamine pathway in the pathogenesis of insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have focussed on the effect of PKC on the insulin signalling cascade showing that activation of PKC inhibits insulin-stimulated glucose transport in rat heart and skeletal muscle and rat adipocytes [21,29,37]. Taken together, in vitro studies indicate that acute increases in glucose induce activation of PKC which, on one hand, induces insulin-independent glucose uptake and, on the other hand, could mediate insulin resistance.…”
mentioning
confidence: 99%
“…As noted above, Sp1 is activated by both conventional and atypical PKC isoforms (63,64) as well as ERK (65), a downstream target of PKC. Filippis et al (79) suggested that glucosamine activates PKC in adipocytes. It has been reported that in mesangial cells, 12 mmol/l glucosamine-a higher concentration than used in the present experiments-caused membrane translocation of several PKC isoforms within hours (80).…”
Section: Discussionmentioning
confidence: 99%